Buccal mucosa micronuclei counts in relation to exposure to low dose-rate radiation from the Chornobyl nuclear accident and other medical and occupational radiation exposures - D. Bazyka; S. C. Finch; I. M. Ilienko; O. Lyaskivska; I. Dyagil; N. Trotsiuk; N. Gudzenko; V. V. Chumak; K. M. Walsh; J. Wiemels; M. P. Little; L.B. Zablotska (BMC, 2017)
Abstract Background Ionizing radiation is a well-known carcinogen. Chromosome aberrations, and in particular micronuclei represent an early biological predictor of cancer risk. There are well-documented associations of micronuclei with ionizing radiation dose in some radiation-exposed groups, although not all. That associations are not seen in all radiation-exposed groups may be because cells with micronuclei will not generally pass through mitosis, so that radiation-induced micronuclei decay, generally within a few years after exposure. Methods Buccal samples from a group of 111 male workers in Ukraine exposed to ionizing radiation during the cleanup activities at the Chornobyl nuclear power plant were studied. Samples were taken between 12 and 18 years after their last radiation exposure from the Chornobyl cleanup. The frequency of binucleated micronuclei was analyzed in relation to estimated bone marrow dose from the cleanup activities along with a number of environmental/occupational risk factors using Poisson regression adjusted for overdispersion. Results Among the 105 persons without a previous cancer diagnosis, the mean Chornobyl-related dose was 59.5 mSv (range 0-748.4 mSv). There was a borderline significant increase in micronuclei frequency among those reporting work as an industrial radiographer compared with all others, with a relative risk of 6.19 (95% CI 0.90, 31.08, 2-sided p = 0.0729), although this was based on a single person. There was a borderline significant positive radiation dose response for micronuclei frequency with increase in micronuclei per 1000 scored cells per Gy of 3.03 (95% CI -0.78, 7.65, 2-sided p = 0.1170), and a borderline significant reduction of excess relative MN prevalence with increasing time since last exposure (p = 0.0949). There was a significant (p = 0.0388) reduction in MN prevalence associated with bone X-ray exposure, but no significant trend (p = 0.3845) of MN prevalence with numbers of bone X-ray procedures. Conclusions There are indications of increasing trends of micronuclei prevalence with Chornobyl-cleanup-associated dose, and indications of reduction in radiation-associated excess prevalence of micronuclei with time after exposure. There are also indications of substantially increased micronuclei associated with work as an industrial radiographer. This analysis adds to the understanding of the long-term effects of low-dose radiation exposures on relevant cellular structures and methods appropriate for long-term radiation biodosimetry.